Validation of the Foot and Ankle Outcome Score (FAOS) for Ankle Osteochondral Lesions - Raymond J. Walls MD, FRCS; Mohammad T. Azam BS; Scott J. Ellis MD; John G. Kennedy MD, FRCS(Orth) (Foot & Ankle Orthopaedics, 2022)
Category: Sports; Ankle Introduction/Purpose: Subjective patient-reported outcome scores are routinely used to evaluate the efficacy of surgical interventions however to date none have been validated for ankle osteochondral lesions (OCL's). The foot and ankle outcome score (FAOS) is a 42 item subjective questionnaire consisting of 5 domains: pain, symptoms, function in daily activities, function in sports, and quality of life. It has been recently validated for flatfoot deformity and hallux valgus correction. The aim of this study was to validate the FAOS for ankle OCL's. Methods: Patients diagnosed with ankle OCL's from 2008 to 2013 were identified through the hospital foot and ankle registry. A retrospective analysis was performed to determine construct validity, where the FAOS subscales were compared with corresponding short form-12 (SF-12) subscales. Correlation was deemed moderate if the Spearman's correlation coefficient was .4 to .7. Preoperative and postoperative scores of 54 patients with OCL's were compared to determine responsiveness. Content validity was prospectively assessed in 20 patients by a separate questionnaire where patients rated the relevance of each FAOS question to their ankle OCL. A score of 2 or more was considered acceptable. Both retrospective analysis and prospective evaluation of 44 patients were used to assess test-retest reliability, which was measured using intraclass correlation coefficients (ICC's). Results: All of the FAOS subscales demonstrated moderate correlation with the physical health component of the SF-12. The FAOS symptoms subscale showed the least correlation, demonstrating the foot-specific nature of the questionnaire. Mental health related domains demonstrated poor correlation. All five FAOS domains are significantly responsive to change in postoperative patients (p<0.01). All domains have acceptable content validity overall, with quality of life (QoL) and function in sports the highest. Test-retest reliability was very good for all domains with ICC's above 0.8. Conclusion: Patient-based assessments have become increasingly important in evaluating treatment effectiveness. This study has shown that the FAOS has very good construct and content validity, reliability, and responsiveness in patients with ankle OCL's. We support its use and consider it a useful patient-based instrument for the assessment of surgical intervention